Empowering PKK Dasawisma Mawar 1 Tosari through Appropriate Technology for Potato Chip Business Development (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aimed to empower women members of the PKK Dasawisma Mawar 1 group in Tosari Village, Pasuruan Regency, by integrating appropriate technology with entrepreneurship and digital-marketing capacity building. The intervention introduced a semi-automatic potato-slicing machine (35–50 kg/hour). It provided a series of training sessions on machine operation, product innovation, basic financial record-keeping, packaging, and online promotion. A participatory, educational, and applicative approach was applied over four months involving 15 group members. After implementation, slicing time decreased from approximately 2–3 hours to 45 minutes per 50 kg of potatoes; drying time and oil content were reduced, yielding crisper chips with extended shelf life. Weekly production rose from about 50–60 to 90–100 packages (≈70% increase). Partners adopted basic management practices and diversified product flavors, while market reach expanded through social media. The program demonstrates that culturally appropriate technology, combined with hands-on training and participatory methods, can significantly improve productivity, product quality, and the entrepreneurial capacity of rural women micro-enterprises, contributing to inclusive local economic development and SDG 8 (Decent Work and Economic Growth).